Multi-Scale Measurements in Blood Rheology - Le, Andy Vinh (Université d'Ottawa / University of Ottawa, 2025)
Blood rheology, governed by the collective behavior of deformable RBC suspended in plasma, remains incompletely understood. This work examines blood flow phenomena at multiple scales, focusing on the interplay between RBC and network geometry, RBC and solute mass transport, and innovative velocity-measurement techniques in dense suspensions. At the scale of the capillary vessels, the transport of blood in uniform networks is explored. The aim of this study is to investigate how the interaction between cells with the individual nodes of the network affects the overall macroscopic transport. Measurements of healthy density-controlled RBC through the network are completed in varying geometry and topology, showing how the excess relative resistance of the network scales non-linearly with the measured flow rate. Defining a capillary number through the local velocity of the cells and an average membrane in-plane shear elasticity, a scaling law for the excess relative resistance as a function of the local volume fraction of RBC and the topology of the network is proposed. The first observations show that these transport properties are likely correlated to the local behavior of RBC and their membrane mechanics. At the arteriolar scale, the influence of RBC on macromolecular mixing in flow is examined. Both aggregated and non-aggregated RBC enhance effective diffusion for increasing flow rates and hematocrit with a maximum near a RBC volume fraction of ~30%. Larger molecules also benefit more from RBC-induced mixing, demonstrating that RBC actively facilitate mass transport in their suspending fluid without relying on pronounced axial migration. Finally, to address the challenge of measuring velocity fields in dense RBC suspensions and to develop a real hemorheophysics of blood, a 2f FCS technique is introduced. Validated with Newtonian and transparent shear-thinning fluids, and applied to physiologically dense suspensions of aggregated and non-aggregated RBC, 2f FCS captures velocity profiles and reveals the transition from parabolic to plug-like flow under varying conditions. Although direct local hematocrit measurements remain challenging, this approach identifies key measurement limitations and lays the groundwork for refined techniques in hemorheology. Collectively, these findings advance the understanding of blood rheology by linking RBC deformation, distribution, and mixing at multiple scales and by providing new measurement strategies for dense, complex suspensions.
Keywords: red blood cell; non-Newtonian; microfluidics; microfluidic network; hydrodynamic resistance; mass transport; mixing; two-foci fluorescence fluctuation